PENGARUH PENATALAKSANAAN RELAKSASI NAPAS DALAM TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS PURWOHARJO COMAL - Nonik Eka Martyastuti; M. Khoirul Iman Yuliyanto (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2019)
Hypertension is a non-communicable disease and one of the risk factors for degenerative diseases such as heart disease, stroke and other blood vessel disease, which is one of the important health problems worldwide because of its high and increasing prevalence, hypertension leads to death by 9 , 4 million annually, hypertension accounts for about 45% of deaths from ischemic heart disease and 51% from stroke. Various risk factors for hypertension include smoking and exposure to cigarette smoke, drinking alcohol, diet / diet, unhealthy lifestyle, obesity, medication, and family history (heredity).Hypertension is a non-communicable disease and one of the risk factors for degenerative diseases such as heart disease, stroke and other blood vessel disease, which is one of the important health problems worldwide because of its high and increasing prevalence, hypertension leads to death by 9 , 4 million annually, hypertension accounts for about 45% of deaths from ischemic heart disease and 51% from stroke. Various risk factors for hypertension include smoking and exposure to cigarette smoke, drinking alcohol, diet / diet, unhealthy lifestyle, obesity, medication, and family history (heredity).The systolic blood pressure of pre test in the treatment group and the p-value control group was 0.651 greater than 0.05 and the post test systolic blood pressure in the treatment group and the p-value control group was 0.000 less than 0.05 , While pre-tested diastolic blood pressure in treatment group and p-value control group was 0.218 greater than 0.05 and postharvest diastolic blood pressure in treatment group and p-value control group of 0.000 was smaller than 0.05.Pre-test systolic blood pressure in the treatment group and the control group did not influence the combination of deep breathing relaxation and progressive muscle relaxation to decreased blood pressure and post-test systolic blood pressure. There was an effect of a combination of deep breathing relaxation and progressive muscle relaxation to blood pressure drop, diastolic blood pressure Pre-test in the treatment group and the control group there was no effect of a combination of deep breathing relaxation and progressive muscle relaxation to the drop in blood pressure and post-test diastolic blood pressure there was an effect of a combination of deep breathing relaxation and progressive muscle relaxation on blood pressure reduction.Combination of deep breathing relaxation and progressive muscle relaxation, Decrease in blood pressure in patients with primary hypertension.